Zooplankton_East_Siberian_Sea_1948_and_1973_Pavshtiks - Russell Hopcroft (Arctic Data Center, 2014)
Zooplankton collected by different expeditions in the East Siberian Sea - August to September 1948 and 1973 are analyzed for species composition, abundance and biomass. Samples were collected with a Juday net using a No 38 silk mesh (168 um) and units are recorded in abundance(#/m3) and biomass (mg/m3). This data was recovered from Pavshtiks, 1994 Composition and Quantitative Distribution of the Zooplankton in the East Siberian Sea. Russian paper with English abstract